Removal of iron, zinc, and nickel-ions using nano bentonite and its applications on power station wastewater. Issue 2 (February 2021) - Ahmed, A.M.; Ayad, Mohamed I.; Eledkawy, Mohamed A.; Darweesh, M.A.; Elmelegy, Essam M.
Abstract: Removal of high concentrations of toxic heavy metals from wastewater is very important within the environmental field because heavy metals pollution a serious environmental problem due to them being nonbiodegradable. This study shed some light on the use of Nano bentonite as an adsorbent for the elimination of Iron, Zinc, and Nickel ions from wastewater, and the optimum conditions were evaluated to find out thermodynamic and kinetic parameters and equilibrium adsorption models have been applied. The results showed that adsorption percentage increases with increasing temperature, speed of rotation, and volume of solution, but decreases with adsorbent dose and initial concentration increase. The adsorption process has fit pseudo-second-order kinetic model Langmuir and Freundlich adsorption isotherm models were applied to analyze adsorption data and both were found to apply to these adsorption processes. Thermodynamic parameters e.g., ΔG o, ΔS o, and ΔH o of the adsorption process were found to be endothermic. Finally, the Nano bentonite was observed to be more powerful for the removal of Fe (III), Zn (II), and Ni (II) at the same experimental conditions. Abstract : Wastewater; Removal of iron, zinc, and nickel; Nano bentonite; Adsorption; Thermodynamic and kinetics parameters; Isotherm models